CONDITIONS FOR BEEKEEPING IN UZBEKISTAN - Shodiyev Murodjon Bakirovich (Modern American Journals, 2025)
From our monographic observation, we see that in the field of beekeeping, which is one of the branches of agriculture, the number of families engaged in beekeeping is increasing. Today, the high demand for bees and their processed products is explained by the presence of medicinal and microelements in them. This, in turn, allows the production of honey and other products (wax, propolis, pollen, beebread, royal jelly and nectar). We can ensure that the income of our independent family farms increases day by day by increasing the production of bee products. Beekeeping is an additional source of income to increase family income and serves to increase the yield of agricultural crops on a personal plot. The article highlights the task of promoting interest among the population in the selection of honey and beekeeping products and conducting independent work to study the industry by increasing the productivity of the bee colony.
Keywords: Branches of agriculture, beekeeping, bee family, bee products, boxwood bees, worker bees working in the hive, worker bees flying in the field, wax, propolis, pollen, beebread, bee milk, bee venom, queen bee, male bee.